A homemade life : stories and recipes from my kitchen table - Wizenberg, Molly (New York : Simon & Schuster, 2009)
Author of the internationally famous blog, Orangette, Molly Wizenberg recounts a life with the kitchen at its center. From her mother's pound cake, a staple of summer picnics during her childhood in Oklahoma, to the eggs she cooked for her father during the weeks before his death, food and memories are intimately entwined.
Includes index.
Keywords: Wizenberg, Molly; Women food writers -- United States -- Biography; Cooking